Safeguarding Giving: The Volunteer and the Intern - Lalor, Eve (Irish Journal of Arts Management and Cultural Policy, 2013)
This paper examines the growing prevalence and status of volunteers and interns in the Irish non-profit cultural sector in the context of rising unemployment and the development of new welfare policies after the 2008 crash, calling for greater transparency and policy development regarding volunteerism in the sector. Levels of volunteering have risen dramatically within the last four years in Ireland. Unemployment in August 2012 was at 14.8%, and 50% of those volunteering are doing so to improve their job prospects. This study examines the growing prevalence and status of volunteers and interns in the Irish non-profit cultural sector. The role that organisational policy may play in the relationship between volunteer and host organisation within the context of the current economic climate is also investigated. The paper concludes that developing a volunteer policy can enable cultural organisations to ethically harness the valuable resource volunteers provide. Further, such policy development is an important stage in the volunteer management cycle for achieving best practice and avoiding job substitution.